British Military Operations in Egypt and the Sudan: A Selected Bibliography - Raugh, Harold E. (Rowman & Littlefield Publishers, 2008)
The British Army's campaigns in Egypt and the Sudan from 1882 to 1899 were among the most dramatic and hard-fought in British military history. In 1882, the British sent an expeditionary force to Egypt to quell the Arabic Revolt and secure British control of the Suez Canal, its lifeline to India. The enigmatic British Major General Charles G. Gordon was sent to the Sudan in 1884 to study the possibility of evacuating Egyptian garrisons threatened by Muslim fanatics, the dervishes, in the Sudan. While the dervishes defeated the British forces on a number of occasions, the British eventually learned to combat the insurrection and ultimately, largely through superior technology and firepower, vanquished the insurgents in 1898. British Operations in Egypt and the Sudan: A Selected Bibliography enumerates and generally describes and annotates hundreds of contemporary, current, and hard-to-find books, journal articles, government documents, and personal papers on all aspects of British military operations in Egypt and the Sudan from 1882 to 1899. Arranged chronologically and topically, chapters cover the various campaigns, focusing on specific battles, leading military personalities, and the contributions of imperial nations as well as supporting services of the British Army. This definitive volume is an indispensable reference for researching imperialism, colonial history, and British military operations, leadership, and tactics.